Study of Different Gain Medium in Open-cavity Multi-wavelength Brillouin-Raman Fiber Laser - Ismail A.; Aminuddin M.A.M.; Sulaiman A.H.; Abdullah F.; Jamaludin M.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Dispersion compensation; Fiber amplifiers; Fiber lasers; Brillouin; Brillouin fiber laser; Dispersion compensating fibers; Gain medium; Laser performance; Multi wavelength fiber laser; Multiwavelength; Open cavity; Raman amplifier; Raman fiber lasers; Fibers